2003
DOI: 10.1068/p3474
|View full text |Cite
|
Sign up to set email alerts
|

Saccadic Suppression of Displacement: Effects of Illumination and Background Manipulation

Abstract: In contrast to other functions which are suppressed during saccades, saccadic suppression of displacement (SSD--a decrease in sensitivity to visual displacements during saccades) has often been considered to be due to efferent processes rather than to visual masking. The aim of this study was to explicitly assess the importance of visual conditions in SSD. In two experiments, a small computer-generated target made random horizontal jumps. An infrared eye tracker was used to detect the saccade toward the new po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The detection rate was higher than we expected based on previous reports from which detection probability could be inferred (Irwin 1992;MacAskill et al 2003;Triesch et al 2003). In this experiment, subjects were encouraged to view the scenes freely and to make many saccades.…”
Section: Resultsmentioning
confidence: 40%
See 4 more Smart Citations
“…The detection rate was higher than we expected based on previous reports from which detection probability could be inferred (Irwin 1992;MacAskill et al 2003;Triesch et al 2003). In this experiment, subjects were encouraged to view the scenes freely and to make many saccades.…”
Section: Resultsmentioning
confidence: 40%
“…We conWrmed that observers are not sensitive to such displacement when it occurs during a saccadic eye movement. This conWrms earlier Wndings of saccadic suppression of displacement with smaller, simpler stimuli 3 (Bridgeman et al 1975;Li and Matin 1997;MacAskill et al 2000MacAskill et al , 2003Anand and Bridgeman 2002;Deubel et al 2004). Bridgeman and Fisher (1990) reported that sensitivity to trans-saccadic target displacement depended on target eccentricity with more suppression for central than peripheral targets.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations